Enhancement of Antibacterial Efficiency of Face Masks Using Metal Nanoparticles (Journal of Pharmaceutical Negative Results, 2022)
In this study, the antibacterial activity of commercial face masks made from polypropylene against gram-negative and positive bacteria was enhanced by dipping in gold nanoparticle (Au NPs) prepared in water using simple chemical precipitation route. The XRD for mask sample shows the typical diffraction lines of polypropylene for untreated mask, compared to samples soaked in the Au NPs suspensions at different concentrations which showed small peaks of gold structure. These diffraction peaks increased in intensity with the concentration of Au NPs in the samples. The strain-stress study shows slightly increasing the sample strength with increasing the Au NPs concentration, while the maximum strain reduced. The antibacterial efficiency of mask soaked in the Au NPs displays a decent inhibition zone toward E. coli and S. aureus bacteria, of diameter about 2.4 cm, and 2 cm respectively. The variation in efficiency of killing comes from the different nature of the composition of these two species.